2015
DOI: 10.3390/molecules201018777
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytoprotective Effects and Antioxidant Capacity of Phenolic Compounds from the Leaves of Swietenia macrophylla

Abstract: Swietenia macrophylla (mahogany) is a highly valued timber species, whereas the leaves are considered to be waste product. A total of 27 phenolic compounds were identified in aqueous extracts from mahogany leaves by comparing retention times and mass spectra data with those of authentic standards using LC-ESI-MS/MS. Polyphenols play an important role in plants as defense mechanisms against pests and pathogens and have potent antioxidant properties. In terms of health applications, interest has increased consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
18
0
2
Order By: Relevance
“…Nevertheless, in other study from leaves aqueous extract of Swetenia were identified nine phenolic acids and 18 flavonoids with antioxidant ability on cell culture, suggesting a cytoprotecting activity (32).…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, in other study from leaves aqueous extract of Swetenia were identified nine phenolic acids and 18 flavonoids with antioxidant ability on cell culture, suggesting a cytoprotecting activity (32).…”
Section: Discussionmentioning
confidence: 90%
“…All plant extracts, except S.sodomaeum, did not significantly affect cells viabilityat concentration up to 400 µM ( Figure 2a).Indeed, incubation of PC12 cells with 5 µM Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) , for 24 h decreased the cell viability compared to control to 44% (Figure 2b). In order to evaluate the protective effect of extracts, Aβ was added to PC12 cells simultaneously to the extracts (100, 200 and 400 µg/ml).…”
Section: Neuroprotective Activity Of Methanolic Extractsmentioning
confidence: 94%
“…The assay was developed in triplicate and calculations based on a calibration curve obtained with gallic acid. The results were expressed as milligram of gallic acid equivalents (GAE) per g of dry extract [29].…”
Section: Folin-ciocalteau Assaymentioning
confidence: 99%
“…LC-MS analysis was performed on a XEVO G2-STof Mass Spectrometer (Waters Corp., Milford, MA, USA). The acquisition parameters and chromatographic analysis were described in details previously, with some adjustments, for example, at the time of gradient elution to 20 minutes instead of 10 [29].…”
Section: Liquid Chromatography Analysis Coupled With High Resolution mentioning
confidence: 99%